Work-family balance of Indian women software professionals: A qualitative study - Valk, Reimara; Srinivasan, V. (2011)
One of the significant changes witnessed in the labour markets in India has been the entry of women IT professionals in the rapidly growing software services sector. As the women take on the role of working professional in addition to their traditional role of the homemaker, they are under great pressure to balance their work and personal lives. This study attempts to understand how work and family related factors influence the work-family balance of Indian women IT professionals. The study is based on an exploratory qualitative study of 13 women IT professionals in the software sector in Bangalore, India. The narratives reveal six major themes: familial influences on life choices; multi-role responsibilities and attempts to negotiate them; self and professional identity; work-life challenges and coping strategies; organisational policies and practices; and social support. © 2010.